Effect of General Anesthesia Combined with Transversus Abdominis Plane Block on Postoperative Sleep Disorders in Elderly Patients Undergoing Gastrointestinal Tumor Surgery: A Prospective, Randomized Controlled Trial - Pu J; Guo C; Xiao Y; Cao Y; Liu Z; Jin Y; Hu Y (Nature and Science of Sleep)
Jie Pu,1 Chendong Guo,1 Yue Xiao,2 Yanan Cao,1 Zhenhua Liu,3 Yuzhong Jin,3 Yimin Hu4 1Department of Anesthesiology, The Second People’s Hospital of Changzhou, Nanjing Medical University, Changzhou, 213003, People’s Republic of China; 2Department of Anesthesiology, Sichuan Cancer Hospital, Chengdu, 100062, People’s Republic of China; 3Changzhou Wujin Hospital of Traditional Chinese Medicine, Changzhou, 213161, People’s Republic of China; 4Department of Anesthesiology, Hospital for Skin Diseases (Institute of Dermatology), Chinese Academy of Medical Sciences & Peking Union Medical College, Nanjing, 210042, People’s Republic of ChinaCorrespondence: Yimin Hu, Department of Anesthesiology, Hospital for Skin Diseases (Institute of Dermatology), Chinese Academy of Medical Sciences & Peking Union Medical College, Nanjing, 210042, People’s Republic of China, Tel +86 18951767577, Email guyueym@njmu.edu.cnPurpose: The aim of this study was to investigate the effect of general anesthesia combined with transversus abdominis plane block on postoperative sleep disorders in elderly patients undergoing gastrointestinal tumor surgery.Methods: For elderly patients with gastrointestinal malignant tumors, we recruited 94 patients, aged 65– 80, who were scheduled for radical laparoscopic surgery. Using the random number table method, the patients were randomly divided into two groups, the general anesthesia group (group GA) and the general anesthesia combined with transversus abdominis plane block group (group GT). The group GA received the sedation-aspiration complex general anesthesia regimen, while the group GT underwent bilateral transversus abdominis plane blocks (TAPB) after the same induction of anesthesia. Group GA was injected bilaterally with equal amounts of saline in the same way. Sleep was monitored using wearable devices on the first day before surgery (P1) and the first and third day after surgery (D1 and D3). The Pittsburgh Sleep Quality Index(PSQI) scale was used to assess sleepiness and the occurrence of postoperative sleep disorders (POSD) on P1, D1 and D3 nights, respectively.Results: Compared to the group GA, the group GT showed a significant decrease in remifentanil use during surgery (P< 0.05). At D1, the group GT showed an increase in the ratio of deep sleep to rapid eye movement sleep (REM), along with a significant decrease in the number of wakefulness (P< 0.05). At D3, the proportion of REM continued to increase and PSQI scores were significantly lower at both D1 and D3 (P< 0.05). In addition, the incidence of POSD and the visual analog scores (VAS) at 0.5h and 6h postoperative activity in D1 showed a decreasing trend (P< 0.05). However, no significant differences were observed between the two groups in general condition, intraoperative condition, remedial analgesia and number of analgesic pump presses (P> 0.05).Conclusion: General anesthesia combined with transversus abdominis plane block reduces the dosage of opioids in abdominal surgery, especially gastrointestinal surgery, alleviates postoperative pain in elderly gastrointestinal oncology patients, improves sleep quality, and reduces the incidence of sleep disorders.Keywords: transversus abdominis plane block, sleep disorders, elderly, gastrointestinal tumors, Pittsburgh sleep quality index